ChemInform Abstract: Substrate Directed C—H Activation for the Synthesis of Benzo[c]cinnolines Through a Sequential C—C and C—N Bond Formation. Issue 50 (December 2015) - Reddy, B. V. Subba; Reddy, C. Ravikumar; Reddy, M. Rajashekhar; Yarlagadda, Suresh; Sridhar, B.
Abstract: The novel strategy is based on an oxidative two‐step transformation of hydrazine dicarboxylates with aryl iodides.